Classical and modern thought on international relations from anarchy to cosmopolis - Jackson, Robert H. 1938- (Palgrave Macmillan, 2005)
In the tradition of the English School of International Relations theory, this project from Robert Jackson seeks to show how continuities in international politics outweigh the changes.
Keywords: Internationale betrekkingen; Politieke ideeën; Internationale Politik; aInternational relations; Politische Philosophie